Status Quo and Influencing Factors of Discharge Readiness of Patients with Bilateral Ureteral Stoma After Radical Cystectomy - Huang, Li; Peng, Shuang (Frontiers in Surgery, 2022)
Bladder cancer is a common malignancy of the urinary system, which occurs mostly in elderly men, and the incidence is increasing year by year. To analyze the status quo and related factors of discharge readiness of patients with bilateral ureteral stoma after radical cystectomy, a retrospective, noncomparative was performed. 544 patients with bilateral ureteral stoma after radical cystectomy in our hospital from December 2018 to December 2020 were selected. The self-designed questionnaire, discharge readiness scale (RHDS) and discharge guidance quality scale (QDTS) were used to investigate the general data, and multiple linear regression was used to analyze the related influencing factors. The total score of RHDS was (72.57 ± 18.56) and the total score of QDTS was (105.63 ± 24.18); the total score of RHDS was positively correlated with the total score of QDTS (r = 0.882, p = 0.000); the results of multiple linear regression showed that age, discharge direction and care mode were the main factors influencing the discharge readiness of patients (p < 0.05). In conclusions, the discharge readiness of patients with bilateral ureteral stoma after radical cystectomy is in the medium level, and there is a large space for improvement. Nurses should strengthen the guidance and nursing of patients’ discharge preparation to reduce the incidence of postoperative complications and readmission rate.